Animaker Media On Student Learning Outcomes in Class VII Science Subject of Smp Negeri 1 Watang Pulu - Nasli, Nurul; Tahir, M hijaz; Takdir, Muhammad; M, Usman; Hermansyah, Sam; Lorenzo, Courtois (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
This study uses a quantitative method with the type of experimental research that aims to determine the effectiveness of using Animaker media on learning outcomes in class VII science at SMP Negeri 1 Watang Pulu, Sidenreng Rappang Regency. The population of this study were all 192 students of class VII at SMP Negeri 1 Watang Pulu, and 26 samples were taken. Data collection techniques were carried out based on Slavin's theory (2000), namely observation techniques, documentation techniques, test techniques, and questionnaire techniques. This indicator consists of four, namely the quality of learning, the suitability of the level of learning, intensity, and time. After the data was collected, the data was analyzed and found that the four indicators of the effectiveness of a strategy were passed and had an impact on student learning outcomes in class VII science subjects at SMP Negeri 1 Watang Pulu. Testing the research hypothesis of the data obtained on average from the higher posttest results, namely 81.8 %, while the pretest results were 50.8%. The results of this study indicate that the use of Animaker media in learning science class VII at SMP Negeri 1 Watang Pulu, Sidenreng Rappang Regency, is declared effective.